Clinical relevance of normal and tumour cell radiosensitivity in BRCA1/BRCA2 mutation carriers: A review. Issue 2 (April 2015) - Bernier, Jacques; Poortmans, Philip
Abstract Women harbouring BRCA1/2 mutations are known to be at higher lifetime risk of developing breast cancer than non-carriers. Compared to mastectomy, conservative surgery is also associated, in this patient population, with a higher probability to developing recurrent ipsilateral breast cancer following primary treatment. To reduce these risks, the management of BRCA1/2 – associated cancers has therefore focused on optimal prophylactic and therapeutic interventions at the time of diagnosis. In a recent past, comparative analyses of radiosensitivity levels have been carried out in murine embryos harbouring BRCA1/2 gene mutation and in non-carriers. The fact that a number of these experimental data are in favour of higher radiosensitivity levels in carriers of germline mutations leads to concern regarding the potential consequences of exposure to radiation, especially in terms of excessive toxicity in normal tissues and radiation-induced malignancies. The objective of this review is to determine whether or not the potentially higher radiosensitivity of normal and tumour cells has a clinical relevance in BRCA1/2 mutations carriers in terms of disease control, acute and late adverse events, and tumourigenesis.